The Sustainable Management of a Productive Natural Capital - Julien Xavier Daubanes (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2017)
This paper examines an industry whose economic activity uses a natural capital on which its profit also relies. When such a productive natural capital has a limited capacity to recover from its exploitation, a free market tends to over-exploit it, calling for public intervention. The analysis is relevant, among other examples, to the case of naturebased tourism. I study the sustainable management of a productive natural capital: the conditions under which its exploitation generates maximum long-run social benefits; the various ways in which a regulator can implement such an exploitation; the rent that it generates for the industry; the effect of social discounting and operators' short-termism, etc. Particular attention is given to situations in which the regulator gives more importance to the industry than it does to consumers, as when consumers are foreigners or when the industry generates needed tax revenues. In those contexts, I find that the industry should make more efforts of conservation, rather than less.
Keywords: Q2; L1; H5; 330; Renewable natural resources; Over-exploitation; Optimal regulation; Proindustry regulation; Public revenue needs; Optimum taxation; Nature-based tourism